Erosion rates in Fennoscandia during the past million years. (1st March 2019) - Jansen, J.D.; Knudsen, M.F.; Andersen, J.L.; Heyman, J.; Egholm, D.L.
Abstract: The widespread existence of cosmogenic nuclides accumulated in bedrock prior to the last glaciation demonstrates the limited erosional efficacy of the most recent Fennoscandian and Laurentide ice sheets. Yet the deeper history of erosion in these landscapes repeatedly blanketed by ice remains essentially unknown. Here we present the first comprehensive ice sheet-wide analysis of cosmogenic 10 Be data (n = 953) from the Fennoscandian landscape. We find 64% of all sampled bedrock surfaces contain 10 Be inheritance, including >85% of blockfields and tors, and >50% of ice-carved terrain, in addition to 27% of ice-transported boulders. Recent ice sheets scoured landscapes well beyond glacial troughs and nuclide inventories reveal a patchy legacy of erosional effectiveness that diminishes at high elevations, such that 89% (n = 55) of bedrock samples retain inheritance above 1600 m. We exploit this widespread nuclide inheritance in a Markov chain Monte Carlo-based inversion model to estimate long-term erosion rates and surface exposure histories from 113 paired 10 Be 26 Al bedrock samples. Nuclide inventories with or without inheritance convey equally important information about the erosional effectiveness of the last ice sheet. We define cosmogenic nuclide memory as the residence time of bedrock samples inside the nuclide-production window (≤2 m depth) where ∼ 80% of the total nuclide production occurs. The cosmogenic nuclide memory is set by mean erosion rate and varies from ∼10 ka for samples eroded >2 m during the last glaciation to > 1-Ma for the slowest erosion rates. We find that mean erosion rates are well constrained compared to the ratio of exposure to burial. The inclusion of bedrock erosion in our computations thwarts the capacity to constrain surface exposure history or identify former nunataks from paired 10 Be 26 Al data. Ice-carved surfaces reflect diverse erosion histories that are not straightforward to interpret from surficial morphology alone. Relative to the ∼10 mm/kyr benchmark for polar ice masses, we report point-based mean erosion rates that vary by more than three orders of magnitude, with glacial troughs and areal-scour terrain eroding at ∼1 to >100 mm/kyr, blockfields at 0.8–16 mm/kyr, and tors at 0.8–7.7 mm/kyr (5 th –95th percentiles). Highlights: We report an ice sheet-wide analysis of cosmogenic nuclide-based erosion computed via inversion modelling. Cosmogenic nuclide memory varies from ∼10 ka to more than 1-Ma. Recent ice sheets scoured beyond glacial troughs and left a patchy erosional legacy. Surface morphology is often a poor indicator of long-term exhumation history. Inclusion of subglacial erosion thwarts the reliable modelling of exposure history.